PENDIDIKAN TASAWUF IMAM AL-GAZALI - Muhammad Adfan Majdi; Tasmuji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article is a literature research with a qualitative descriptive approach that attempts to describe al-Ghazali's thought process in reconciling sharia and Sufism. This study found that although al-Ghazali did not believe in the existence of Rasa, this did not make him less confident as a tool in achieving the truth. The basis for analyzing and understanding religious problems, while the concept of Ma'rifat as a characteristic of al-Ghazali is the result of the development of previously existing concepts. In his efforts to reconcile sharia and Sufism, al-Ghazali succeeded in explaining the increasingly close similarities between sharia and Sufism, but behind all that, al-Ghazali was not very successful in placing both on the same level. This can be seen from the stratification - lay and caring - of Muslims who do good deeds, so that they do not realize they are walking towards a tendency towards Sufi superiority.